Improvement of an Effective Data Emplacement and Redistribution Algorithm among Nodes in Cloud Based Environment - Annapoorani, S; Srinivasan, B (International Journal of Computer Sciences and Engineering, 2025)
This paper is concerned with the study and analysis of Data Emplacement and Redistribution (DER) in large set of databases called Big Data and proposes a model for improving the efficiency of data processing and storage utilization for dynamic load imbalance among nodes in a heterogeneous cloud environment. With the era of explosive information and data receiving, more and more fields need to deal with massive, large scale of data. A method has been proposed with an improved Data Placement algorithm called Effective Data Emplacement and Redistribution approach (EDER) with computing capacity of each node as a predominant factor that promotes and improves the efficiency in data processing in a short duration time from large set of data. The proposed solution improves the performance of the heterogeneous cluster environment by effectively distributing data based on the performance oriented sampling as the experimental results made with word count applications